Qualidade e metabolismo antioxidante em frutos de clones de aceroleira armazenados a 4 e 8 ºC. - Maciel, Vlayrton Tomé (2012)
The present work aimed to study the effect of fruit storage of six clones of acerola (BRS 152 BRS 235 BRS 236 BRS 237 BRS 238 and II47/1) at temperature below the temperature minimum security (TMS), analyzing the effects on fruit quality, the content of bioactive compounds and enzyme activity. The fruits were harvested at the beginning of ripening stage on the experimental field of Embrapa Tropical, in the city of Pacajus being packed in plastic trays involved with PVC film, which were stored in cold storage at temperatures of 4 °C and 8 °C for up to 12 days. Every three days samples were withdrawn (tray containing about 180 g of fruit) for carrying out analyzes, and the fruits are then subjected to a processing multiprocessor 1 mm screen to obtain the pulp. The experimental design was completely randomized in factorial scheme 6 x 5 with three replications, with the first factor corresponding to six clones of acerola and the second one corresponding to the five times of fruit storage (0, 3, 6, 9 and 12 days). The data were subjected to analysis of variance and, when the interaction between the two factors was significant, they were subjected to regression analysis; when there was no significant interaction, the means were compared by Tukey’s test at 5% of probability. To assess the quality of fruits, it was analyzed their physical (strength, weight loss and color) and physico-chemical and chemical characteristics (pH, soluble solids, titratable acidity and total soluble sugars). As a result, it was observed that the characteristics of the fruit stored at 4 °C to 8 °C were practically the same, except with respect to mass loss, which was 31% lower at 4 °C. Therefore, in general, the fruit storage at 4 °C did not affect the quality parameters of fruits, compared to those stored in the TMS to the acerola (8 °C). Regarding the content of bioactive compounds (ascorbic acid, carotenoids and anthocyanins), the fruit stored at 4 °C, generally did not differ from that of the fruit stored at 8 °C. There was a trend towards a decrease in the ascorbic acid content during storage at both temperatures, a result also observed for the anthocyanins to 8 °C. On the other hand, the carotenoid content increased at 4 °C and did not change with time of storage at 8 °C. The fruits of clone II47/1 had the higher contents of ascorbic acid, carotenoids and anthocyanins in the two storage temperatures. In general the phenol oxidizing enzymes (polyphenol oxidase and guaiacol peroxidase) of fruit clones stored at 4 and 8 °C had similar behavior during cold storage, and the fruits of clones II47/1 and BRS 152 had the higher enzyme activity during storage at both temperatures The study about the antioxidant enzymes (superoxide dismutase catalase and ascorbate peroxidase) revealed that fruits stored at 4 °C showed respectively activity values of superoxide dismutase and catalase 263% and 37% on average higher than those stored at TMS for acerola (8 °C) These results suggest that the fruits storaged at 4 °C are under oxidative stress Catalase was the main hydrogen peroxide removing enzyme in fruit which activity increased after 6 days of storage The results suggest that clones II47 / 1 and BRS 152 are resistant storage conditions at temperatures 4 and 8 °C.